Note to “The Theory of Evolution in contemporary culture”, of Giorgio Forti (25/10/13) [with english version] (Nóema, 2013)
It has never existed for us a world without any relationship to our cognitive sciences  and to our words. Natural sciences, like all sciences in general, are made of a series of historical operations.
Keywords: Biological evolution; social evolution; personal history; relationship mind-body; Edmund Husserl; historical operations.